Exosomes from Hypoxic Mesenchymal Stem Cells Enhance TGF-β Expression and Promote Collagen Regeneration in Wistar Rats with Collagen Loss - Kusumawardani, Ade Ifalliah Putri; Subchan, Prasetyowati; Sumarawati, Titiek; Setiawan, Eko (Molecular and Cellular Biomedical Sciences, 2025)
Background: Ultraviolet B (UVB) exposure triggers reactive oxygen species (ROS) formation, inhibits procollagen synthesis via the transforming growth factor-beta (TGF-β)/Smad pathway, and leads to collagen loss. Exosomes derived from hypoxia-conditioned mesenchymal stem cells (EH-MSCs) are more effective than those from normoxic MSCs due to their higher content of miRNAs and cytokines with anti-inflammatory and regenerative properties. This study aims to evaluate the effect of EH-MSC injection on TGF- β levels and collagen density in Wistar male rats with UVB-induced collagen loss. Materials and methods: This in vivo experimental study used a post-test only control group design with 30 rats, divided into five groups: Healthy group, 0.9% NaCl-treated group, hyaluronic acid (HA)-treated group, 200μL EH-MSC-treated group, and 300μL EH-MSC-treated group. TGF-β levels were analyzed using ELISA, while collagen density was assessed with Masson trichrome staining.Results: Highest mean TGF-β levels were observed in the 300μL EH-MSC-treated group (155.56±99.84 pg/mL), while the highest collagen density was found in the Healthy group (23.07±1.81 pg/mL). Mann-Whitney test indicated a significant increase (p=0.008) in TGF-β levels in treatment groups compared to the 0.9% NaCl-treated group. Post Hoc LSD Tamhane test for collagen density also showed a significant increase (p=0.000) in treatment groups compared to the 0.9% NaCl-treated group. Conclusion: EH-MSC injection significantly increased TGF-β levels and collagen density, indicating its potential for promoting skin repair in UVB-induced collagen loss.Keywords: EH-MSC, collagen loss, TGF-β, collagen density